Exploring the Influence of Forensic Accounting Techniques on the Market Value of Selected Deposit Money Banks in Nigeria - Dagunduro, Muyiwa; Boluwaji, Olayinka; Ajayi, Joseph; Falana, Gbenga (The Journal of Accounting and Management, 2024)
Abstract: Market value, a key indicator of investor confidence, reflects not only the financial performance but also the broader sentiment within the financial market. By examining how forensic accounting techniques influence market value, this study aims to unravel the nuanced impact of these practices on the banking industry's standing and investor perceptions. Data were sourced from annual records of deposit money banks listed on the Nigerian Exchange Group (NGX). The study focused on a population of ten (10) selected deposit money banks listed on NGX. The study employed a census sampling technique and the total population was investigated. The collected data in this study underwent analysis using both descriptive and inferential statistical methods. This study revealed that forensic accounting techniques exhibit a positive and significant effect on the market value of deposit money banks in Nigeria. This implies that the application of forensic methods holds meaningful influence, garnering positive responses from investors and the market at large. It was concluded that the positive and significant impact of forensic accounting techniques underscores their meaningful influence on market value, emphasizing their importance in financial practices. This study therefore recommends that banks should consider investing in forensic accounting techniques to bolster their financial practices and enhance market value.